(untitled) (Integral Research, 2025)
Kampilya, identified with modern-day Kampil in Uttar Pradesh, was a prominent city during the Mahabharata era and served as the capital of the Panchala kingdom. Archaeological findings, including coins, statues, and ancient fort ruins, highlight its historical significance. The region, situated along the Budhi Ganga River, is associated with King Drupada and events like Draupadi’s swayamvara. Texts like the Mahabharata, Puranas, and Brahmanas describe Panchala as a prosperous and culturally advanced kingdom, divided into North and South Panchala. The area also played a crucial role in resisting Turkic invasions during the medieval period, showcasing its enduring martial spirit. The legacy of Kampilya remains preserved in local folklore and historical sites.